2021
DOI: 10.1590/1981-6723.34519
|View full text |Cite
|
Sign up to set email alerts
|

Texture profile of surimi-like material from mechanically deboned turkey meat

Abstract: The study aimed to evaluate the textural properties of turkey surimi-like (TSL) gels from mechanically deboned turkey meat (MDTM) by washing procedures. The effects of water, sodium chloride, sodium bicarbonate, and potassium phosphate buffer washing solutions, cycles, and salt addition were investigated. Sodium bicarbonate washing solution produced lightened and whitened cooked gels. Addition of salt reduced (p < 0.05) cooking loss and increased (p < 0.05) hardness and chewiness. TSL gels from sodium bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(44 reference statements)
0
4
0
1
Order By: Relevance
“…The turkey surimi‐like (TSL; 13.82% protein, 78.94% moisture, 2.53% fat, and pH = 7.99) material used as ingredient in the present work was obtained by two cycles of MDTM washing with 0.06 M sodium bicarbonate solution (NaHCO 3 ) as recommended by Massingue et al (2019). The washing process has stated to produce low‐fat whitish and flavorless surimi‐like material with high water holding capacity (Massingue et al, 2019) and low cooking loss during gel formation (Massingue et al, 2021). For each replication (products batch), the TSL material was obtained and stored at 4°C for no longer than 3 h before use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The turkey surimi‐like (TSL; 13.82% protein, 78.94% moisture, 2.53% fat, and pH = 7.99) material used as ingredient in the present work was obtained by two cycles of MDTM washing with 0.06 M sodium bicarbonate solution (NaHCO 3 ) as recommended by Massingue et al (2019). The washing process has stated to produce low‐fat whitish and flavorless surimi‐like material with high water holding capacity (Massingue et al, 2019) and low cooking loss during gel formation (Massingue et al, 2021). For each replication (products batch), the TSL material was obtained and stored at 4°C for no longer than 3 h before use.…”
Section: Methodsmentioning
confidence: 99%
“…This process involves washing the meat with water or weak strength ionic salt solutions several times, removing fats and pigments as well as concentrating myofibrillar proteins, in order to obtain a colorless material with good technological properties, lower fat content, and long shelf-life (Cortez-Vega et al, 2013;Stangierski et al, 2013). The surimi-like material possesses some important functional properties such as gel forming ability and water holding capacity due to its content of myofibrillar proteins, which are mainly responsible for gel and emulsion forming that stabilize the comminuted and restructured meat products (Massingue et al, 2019(Massingue et al, , 2021.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that F4 is the best mixed-species formula for the raw material of surimi. Higher hardness and chewiness is attributed to the higher protein and lower moisture content (Massingue et al, 2021). Gel strength of the surimi is directly correlated with hardness (Tanuja et al, 2014).…”
Section: Textural Profilementioning
confidence: 99%
“…Hasil uji derajat putih surimi ikan nila menunjukan nilai tertinggi pada perlakuan D sebesar 66,94%, sedangkan yang terendah pada perlakuan A sebesar 53,40%. Nilai derajat putih terbaik pada penelitian ini dapat dikategorikan sebagai surimi kelas I seperti disebutkan oleh Massingue et al (2021) bahwa syarat derajat putih pada surimi kelas I memiliki nilai index lebih dari 46%.…”
Section: Derajat Putihunclassified